Increasing Self Efficacy Behavior Prevention of Transmission and Compliance with Tuberculosis Medication through Health Promotion: A Systematic Review - Munawaroh, Intan; Kurniawati, Ninuk Dian; Purwaningsih, Purwaningsih; Romantika, Dwi Dina; Karingga, Devangga Darma (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
Self efficacy, behavior and compliance are very important factors in achieving optimal health status in pulmonary TB patients. Health promotion, improveself efficacy, transmission prevention behavior and adherence to taking TB drugs are some of the factors that can support the Tuberculosis control program. The purpose of this systematic review is to determine the effectiveness of health promotion toself-effi cacy, transmission prevention behavior and compliance with tuberculosis medication. Search for articles using the PICOT framework in the database; Ebscho, Science direct, Sage Journals, Scopus, Pubmed, restricted to the last 5 years; 2015 to 2020, there were 16 international journals. Journal design criteria used prospective study, cross sectional study and RCT. The number of samples from the study varied from 27 to 1.213 respondents. Based on the results of the study, there are six methods, namely conventional health promotion, health promotion training, digital health promotion training, online videos about tuberculosis, SMS and traditional language educational videos via DVD. The patient’s Self-efficacy can be seen when the patient has received digital health education and health promotion. On conventional methods and SMS can improve behavior and compliance, Prevention of transmission and adherence to taking medication in TB patients. The most effective method is using conventional methods that apply direct implementation or direct interaction between health promotion providers and participants.